Interactive Learning Innovation through Puzzle Media: A Solution to Improve Student Literacy - Ghozali, Solchan; Yuliastutik, Yuliastutik; Mardikaningsih, Rahayu; Darmawan, Didit; Al Laisty, M. Dikhyah; Nafiin, Muhammad Wihdatun; Thaha, Amatillah (Bulletin of Science, Technology and Society, 2022)
Reading ability is a very important basic competency for elementary school students. This research explores the potential of puzzle media as an innovative learning tool to improve students' reading skills. Using the literature study method, this research identifies the advantages of puzzle media, such as the ability to create an interactive, fun and motivating learning experience for students. Various types of puzzles, such as crossword puzzles, jigsaw puzzles and word puzzles, have proven effective in helping students understand letters, words and sentences in a fun way. The implementation of puzzle media faces several challenges, including limited teacher understanding, diverse student characteristics, and lack of parental involvement. Collaboration between teachers, students and parents is key to overcoming these obstacles. This study recommends teacher training, a variety of puzzle media, as well as parental involvement in supporting learning at home. Further research is needed to quantitatively evaluate the effectiveness of puzzle media and integrate it into the basic education curriculum. With an integrated approach, puzzle media can be an effective tool in improving students' reading skills and contribute to improving the quality of education in Indonesia.